Uso de taninos de espécies florestais no tratamento de água para abastecimento - Sousa, Thaís Brito (2015)
The Cerrado is the second largest biome in South America and the savanna with the greatest biodiversity in the world, however, it is considered a "hotspot" mainly by the great timber exploitation intended for charcoal production. With the use restrictions of the charcoal from native forests, it has become necessary searching for alternative sources for the timber socioeconomic destination, which highlights the use of bark. One of the main bark products are tannins, secondary metabolites that can be for several purposes, such as coagulant in water treatment. Despite the advantages of using this biodegradable material, is still little known about the best extraction conditions and the tannins potential of the Brazilian species, and even less is known about the performance of these species in water treatment. In this study the objective was to investigate the influence of time and sodium sulfite concentration in the income in tannins in the bark of two forest species of the Cerrado (Anadenanthera pelegrina and Tachigali aurea), propose appropriate conditions of extraction of these species and use the tannins obtained from these barks as a natural coagulant in treating water for supply. Barks from the species were collected in the municipality of Barreiras-BA, they were dried, crushed and the material moisture was determined. The extraction followed the methodology used by Mori F. et al (2003), varying the time (2, 3 and 4 hours) and the sodium sulfite amount (0, 1, 2, 3 and 4%). The water treatment was carried out by Jartest equipment, where the tannins were mixed with aluminum sulfate and ferric chloride in different ratios. For virtually every parameter analyzed in both species, the influence of time and sodium sulfite were significant. For Anadenanthera peregrina indicated to 2:50 hours and the concentration of 3.6% sodium sulfite for obtaining increased yield in condensed tannins and for Tachigali aurea 3:03 hours and 5.8 % sodium sulfite. In water treatment, it was found that when it was used tannins separately or with chemical coagulants the turbidity followed standard of clarify the raw water, with very low efficiency. One of the reasons is because the material has not undergone chemical modification. In relation to pH it was found that tannins have not changed the same, differently from chemical reagents, this being interesting feature in treating water for supply.